Cognitive Modelling of Service Design Team Based on Genetic Algorithms - Weiguo, Zhang; Khiatthong, Tongchue (Journal of Ecohumanism, 2024)
Currently, the development of the world economy plays a prominent role in the service industry. Modeling the service industry is an important issue that focuses on the service sector. Therefore, this study created a cognitive model for a service design team and how to build a team based on it. These models and methods aim to promote and realize commercial and social value innovations in service design. However, this study sets two objectives by focusing on the process and analysis as follows: (1) studying the process of cognitive mechanisms for service design and (2) analyzing and designing a model for the establishment of a service design team. This method defines the main focus of the service design team management study using genetic algorithms that search based on the probability of motivation. The process involves designing and creating a cognitive model for services using genetic algorithms. The results show a team management model designed using cognitive mechanisms. These models and methodologies promote the realization of innovative commercial and social value in service design, resulting in satisfactory and reliable results.